Real-world study for the optimal charging of electric vehicles - Emmanouil D. Kostopoulos; George C. Spyropoulos; John K. Kaldellis (Energy Reports, 2020)
Electric Vehicles (EVs), accompanied with the use of Renewable Energy Sources (RES), are the solution for the decarbonization of the transport sector and are undoubtedly on the rise. Although EVs have been in the limelight over the last decade, little effort has been made towards the proper use of the vehicle's battery. Therefore, a better understanding of Lithium-ion (Li-ion) batteries, since they represent the heart of the majority of electric cars, during the discharging and charging procedure is crucial. The present study, that was experimentally conducted under real-world driving conditions, quantitatively analyzes the energy losses that take place during the charging of a Battery Electric Vehicle (BEV), focusing especially in the previously unexplored 80%-100% State of Charge (SoC) area. The results show that losses, during charging within the abovementioned area, are almost double compared to the 20%-80% SoC area and vehicle's average specific real energy consumption is almost 2 kWh/100 km more, compared to what the driver sees on the EV's dashboard. Furthermore, it is not for the driver's benefit to exceed 80% of SoC during charging, considering the required charging time, the distance that each SoC area provides and the life expectancy of the battery itself. Based on these results and after a thorough literature review, the authors suggest the optimum SoC range within which drivers should operate the EV's battery.
Keywords: 330; Electric vehicles; Energy losses; Optimal charging procedure; Real-world experiment; Second life battery market